BUSINESS MODELS OF SOCIAL ENTREPRENEURSHIP IN THE FIELD OF PASSENGER TRANSPORTATION: OPPORTUNITIES AND PROSPECTS FOR APPLICATION - Базилюк , Антоніна; Назаренко, Ярослава (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article examines the concept of social entrepreneurship as an effective tool for solving social problems in the field of passenger transportation. The purpose of the article is to study the possibilities of using business models of social entrepreneurship in the field of passenger transportation. The text analyses the main business models of social entrepreneurship, including the employment model, the profit-generating model with social impact, and the mixed and innovative model. It identifies opportunities for applying these models to enhance transport accessibility, create jobs for socially vulnerable populations, reduce negative environmental impacts, and develop sustainable transport solutions. Additionally, the text outlines the prospects for the development of social entrepreneurship in the transport sector, considering technological innovations, government support, and collaboration with the private sector. The article highlights the identified prospects and opportunities for implementing business models in social entrepreneurship. It emphasizes the necessity of an integrated approach to developing social entrepreneurship within the passenger transportation sector in order to achieve sustainable socio-economic development.